EFEKTIVITAS PELATIHAN PERSONAL SAFETY SKILL SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL PADA REMAJA - Christiana, Elisa (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Background: Sexual violence is sexual behavior that can negatively affect a person's health and quality of life. Indonesia has entered the “sexual violence emergency” phase in the past decade after experiencing a significant spike in cases each year. The impact of victims of sexual violence usually appears several years after the violence occurs such as physical and psychological damage. Objective: to determine the effectiveness of respondents' knowledge before and after training to determine the effectiveness of Personal Safety Skills on the ability to prevent sexual violence. Methods: The study used experimental research with a quasi experimental design of one group pretest posttest design. The population was 17 students of SMP Muhammadiyah 1 Sampang with purposive sampling technique. Data analysis using non-parametric statistical techniques with differential t-test. Results: The results of the paired t test analysis with a p value = 0.001 so that p <0.05 this shows a significant difference between the pre-test and post-test values. Conclusion: Personal Safety Skill is effective to improve the ability to prevent sexual violence in adolescents before training and after training. This shows that children are able to absorb the information provided during training